Commentary on the Judgment of the Court of Justice of the European Union (Grand Chamber) of 04 October C-399/22 (Revista Española de Estudios Agrosociales y Pesqueros, 2025)
Commentary on the Judgment of the Court of Justice of the European Union (Grand Chamber) of 04 October 2024, C-399/22.
Keywords: imports; origin; consumers; common trade policy